2012
DOI: 10.2147/ceg.s29023
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapies for diarrhea-predominant irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) causes gastrointestinal symptoms such as abdominal pain, bloating, and bowel pattern abnormalities, which compromise patients’ daily functioning. Common therapies address one or two IBS symptoms, while others offer wider symptom control, presumably by targeting pathophysiologic mechanisms of IBS. The aim of this targeted literature review was to capture clinical trial reports of agents receiving the highest recommendation (Grade 1) for treatment of IBS from the 2009 American Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 88 publications
0
16
0
2
Order By: Relevance
“…Die Bedenken in Form der Entwicklung einer Antibiotikaresistenz bei einem Krankheitsbild mit hoher Prävalenz in der Bevölkerung sowie chronischem und rekurrierendem Verlauf und damit der potenziellen Notwendigkeit einer wiederholten Therapie teilte auch die FDA, die eine Zulassung für das RDS ohne Obstipation nicht erteilte und weitere Daten zum wiederholten Einsatz des Präparates forderte [13]. Zu diesem Aspekt wurden bislang zwei Berichte publiziert [13,15], nach denen eine wiederholte RifaximinTherapie über 5 oder mehr Kurse effektiv war; die Wiederholungsintervalle lagen im Median zwischen 4 und 12 Monaten.…”
Section: Therapeutische Optionenunclassified
See 1 more Smart Citation
“…Die Bedenken in Form der Entwicklung einer Antibiotikaresistenz bei einem Krankheitsbild mit hoher Prävalenz in der Bevölkerung sowie chronischem und rekurrierendem Verlauf und damit der potenziellen Notwendigkeit einer wiederholten Therapie teilte auch die FDA, die eine Zulassung für das RDS ohne Obstipation nicht erteilte und weitere Daten zum wiederholten Einsatz des Präparates forderte [13]. Zu diesem Aspekt wurden bislang zwei Berichte publiziert [13,15], nach denen eine wiederholte RifaximinTherapie über 5 oder mehr Kurse effektiv war; die Wiederholungsintervalle lagen im Median zwischen 4 und 12 Monaten.…”
Section: Therapeutische Optionenunclassified
“…Zu diesem Aspekt wurden bislang zwei Berichte publiziert [13,15], nach denen eine wiederholte RifaximinTherapie über 5 oder mehr Kurse effektiv war; die Wiederholungsintervalle lagen im Median zwischen 4 und 12 Monaten. Prucaloprid Als Ausblick sei erwähnt, dass der dem Cisaprid sehr ähnliche 5-HT 4 -Rezeptor Agonist Prucaloprid (Resolor ® ), der ebenfalls als Prokinetikum im Gastrointestinaltrakt wirksam ist, in großen, kontrollierten randomisierten Studien eine gute Effektivität in der Therapie der chronischen Obstipation gezeigt hat.…”
Section: Therapeutische Optionenunclassified
“…The pathogenesis of IBS is unclear, but the condition is generally believed to reflect the complex interactions between visceral hypersensitivity, environmental factors, stress, and the effects of altered serotonergic tone on gut motility (13). It is abundantly clear that there is not a single cause of IBS symptoms and the condition should be thought of as a syndrome of symptoms, rather than as a traditional disease state.…”
Section: Introductionmentioning
confidence: 99%
“…Additional etiologies that have been proposed for IBS underscore the wide range of possible causes and include (I) altered gut microbiota; (II) altered immune function; (III) inflammation; (IV) food intolerances; (V) post-infectious sequelae; (VI) impaired gas handling and (VII) altered motility due to volatile bacterial fermentation products (13)(14)(15)(16)(17). Historically, IBS therapies have tended to target single IBS symptoms, e.g., laxatives to treat constipation, anti-diarrheals to treat diarrhea, and anti-spasmodics to treat abdominal pain (13), all of which often fail to provide satisfactory relief of global IBS symptoms. Medications with multiple potential targets, designed to positively affect both gastrointestinal motility and abdominal pain, could be expected to have broader treatment effects than these symptom-directed therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The prevalence of IBS with diarrhea is approximately 3% among the general population in the UK[10] and ranged from 3% to 20% in North America. [11] IBS is more common in women than men. [21213] SEPAHAN systematic review also showed the greater prevalence in women than men.…”
Section: Introductionmentioning
confidence: 99%